2020
DOI: 10.3390/ijerph17051482
|View full text |Cite
|
Sign up to set email alerts
|

The Effects on Inappropriate Weight for Gestational Age of an SMS Based Educational Intervention for Pregnant Women in Xi’an China: A Quasi-Randomized Controlled Trial

Abstract: Background: The aim of this study was to estimate the effects of maternal text messages on inappropriate weight for gestational age (IWGA) in newborns in rural China. Methods: Participants were pregnant women presenting for antenatal care at a Maternal and Child Health Center in Xi’an, China during the 2013–2015 period. In total, 2115 women completed the program with follow-up information included in the final analyses. All mothers were divided into four groups, including (1) a control group that received only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Oladeinde et al ( 22 ) analyzed the prevalence and related risk factors of low-birth-weight newborns delivered by traditional midwives, and found that prevalence was significantly associated with maternal age, gestational age, maternal height, marital status, and time of registration. Zhou et al ( 23 ) have studied the impact of short message information on the inappropriate weight of pregnant women in rural China. A set of free short message information mainly includes good family antenatal operation advice and nursing consultation, thus playing a protective role on macrosomia and preventing inappropriate weight during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Oladeinde et al ( 22 ) analyzed the prevalence and related risk factors of low-birth-weight newborns delivered by traditional midwives, and found that prevalence was significantly associated with maternal age, gestational age, maternal height, marital status, and time of registration. Zhou et al ( 23 ) have studied the impact of short message information on the inappropriate weight of pregnant women in rural China. A set of free short message information mainly includes good family antenatal operation advice and nursing consultation, thus playing a protective role on macrosomia and preventing inappropriate weight during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the overall level of health literacy among Chinese residents was relatively low [ 48 ]. Therefore, health promotion and education may play an important role in patient empowerment, which in turn leads to better self-management of medical conditions, ultimately lowering costs of care [ 33 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an effective tool and intervention method, a series of studies have revealed the positive effects of sending health information by one-way or an interactive way for pre-exposure prevention [4]. SMS can help people manage their health [5,6] and prevent disease [7,8]. In particular, due to its cheaper price, it is feasible to conduct public health interventions in low-and middleincome countries [9].…”
Section: Literature Review: Sms Application Areasmentioning
confidence: 99%
“…SMS can increase the virus re-detection rate and reduce the possibility of disease transmission [11]. For pregnant women, short messages are not only beneficial to the health of a newborn [6], but also maternal health and behaviors [5]. In addition, some unhealthy behaviors (e.g., smoking [12], sedentary [13], excessive calorie intake [14], etc.)…”
Section: Literature Review: Sms Application Areasmentioning
confidence: 99%